Refugees and Immigrants in the Nordic - Buch, Anders; Berthou, Sara Kristine Gløjmar; Bredgaard, Thomas (Nordic Journal of Working Life Studies, 2018)
Immigration to the Nordic countries has increased significantly in the last 40 years (Pettersen & Østby 2013:76). Although exact data are hard to come by, it is clear that the term integration, albeit vague and often undefined, has become central in public and political debates. A central premise of most of the debates is the claim that newly arrived immigrants and refugees have not become part of their host societies to a satisfactory extent. Subsequently, an increasing number of initiatives and laws have been introduced in the Nordic countries with the intention to promote integration. (...)